2018
DOI: 10.1016/j.bcp.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A review of hydrogen sulfide (H2S) donors: Chemistry and potential therapeutic applications

Abstract: Hydrogen sulfide (HS) is a ubiquitous small gaseous signaling molecule, playing an important role in many physiological processes and joining nitric oxide and carbon monoxide in the group of signaling agents termed gasotransmitters. Endogenous concentrations of HS are generally low, making it difficult to discern precise biological functions. As such, probing the physiological roles of HS is aided by exogenous delivery of the gas in cell and animal studies. This need for an exogenous source of HS provides a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
347
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(352 citation statements)
references
References 123 publications
(126 reference statements)
3
347
0
2
Order By: Relevance
“…Consistent with our previous results, our present study first confirmed that DATS significantly inhibited KTC‐1 cells growth and long‐term proliferation in a dose‐dependent manner (Figure ). It is worth noting that DATS serves as a naturally occurring donor of H 2 S (Powell, Dillon, & Matson, ). DATS was reported to be converted into H 2 S in the presence of free thiols by human red blood cells, and DATS treatment led to vasorelaxation of aortic rings and benefited angiocardiopathy (Benavides et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previous results, our present study first confirmed that DATS significantly inhibited KTC‐1 cells growth and long‐term proliferation in a dose‐dependent manner (Figure ). It is worth noting that DATS serves as a naturally occurring donor of H 2 S (Powell, Dillon, & Matson, ). DATS was reported to be converted into H 2 S in the presence of free thiols by human red blood cells, and DATS treatment led to vasorelaxation of aortic rings and benefited angiocardiopathy (Benavides et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…[1] While the actual chemical identity of the signaling molecule produced by these enzymes remains controversial (H 2 Sv s. its closely related sulfur species), we will focus our discussion on H 2 Sfor the purpose of this manuscript. [3] Al arge number of donors with different structures (phosphorthioates, N-mercapton derivatives,t hiocarbamates,a cyld isulfides,t hioamides, gemdithiols,e tc.) [2] Consequently,compounds that can be used to precisely regulate H 2 S concentrations (up and down) are important research tools as well as potential therapeutic agents.Inthis regard, the studies of H 2 S-releasing compounds (or donors) have attracted considerable attention recently.…”
mentioning
confidence: 99%
“…[2] Consequently,compounds that can be used to precisely regulate H 2 S concentrations (up and down) are important research tools as well as potential therapeutic agents.Inthis regard, the studies of H 2 S-releasing compounds (or donors) have attracted considerable attention recently. [3] Al arge number of donors with different structures (phosphorthioates, N-mercapton derivatives,t hiocarbamates,a cyld isulfides,t hioamides, gemdithiols,e tc.) have been developed, along with various triggering mechanisms (thiol-, photo-, pH-, ROS-, or enzyme-triggered).…”
mentioning
confidence: 99%
“…Furthermore, NaHS was used as the most commonly chosen H 2 S donor. Recently, more stable and reliable H 2 S donors are available (Powell, Dillon, & Matson, ), such donors may have been used to determine the therapeutic potency of exogenous H 2 S administration. This model of hypertension with H 2 S treatment may not be served as a promising therapeutic strategy for the successful management of patients with hypertension and ED who have poor or no response to PDE‐5 inhibitors.…”
Section: Discussionmentioning
confidence: 99%